Six Sigma for managers - Brue, Greg (New York, New York : McGraw-Hill Education, 2015)
Overview: Unlock new levels of quality, performance, customer service, and profits. Written specifically for managers with little or no experience on the subject, Six Sigma for Managers, Second Edition, provides step-by-step guidance and examples for implementing a Six Sigma initiative. Written specifically for today's busy manager, Briefcase Books feature eye-catching icons, checklists, and sidebars to guide managers step by step through everyday workplace situations. Updated with the latest in implementation strategies and tactics, tips from insiders in the field, and new stories and insights from the Six Sigma experiences of others. -- Clear definitions of key management terms and concepts. -- Practical advice for minimizing the possibility of error. -- Examples of successful management. -- Specific planning procedures, tactics, and hands-on techniques. -- Greg Brue is CEO of Six Sigma Consultants and is a master six sigma black belt.
Foreword / Mikel J Harry -- Preface -- Introduction To Six Sigma: -- What is six sigma? -- Evolution of the six sigma fundamentals -- What is sigma? -- Essentials of the six sigma methodology -- Focus on engaging people and changing processes -- Not only statistics, but cultural changes -- Six sigma is not -- Manager's Checklist For Chapter 1 -- Defining Quality And Measuring Performance: -- Start with your customers -- Understand your processes -- Determine your metrics -- Essential six sigma formula -- Quality and metrics, first and last -- Manager's Checklist For Chapter 2 -- Right Way To Implement Six Sigma: -- Six sigma: the early years and implementation flaws -- More realistic approach to six sigma -- Readying the organization -- Key players -- Executive leaders and champions -- Champions -- Master black belts -- Black belts -- Green belts -- Communicate! -- Train! -- Infrastructure -- What to expect from outside consultants -- Getting Started: Dos -- Getting Started: Don'ts -- Executive overview of DMAIC -- Manager's Checklist For Chapter 3 -- Define Phase: -- Define phase activities -- Define the phase-gate review -- Summary -- Manager's Checklist For Chapter 4 -- Measure Phase: -- Purposes of the measure phase -- Measure phase activities -- Step 1: Map the process in detail -- Step 2: Create a YX matrix -- Step 3: Perform a failure modes and effects analysis (FMEA) -- Step 4: Conduct a Measurement System Analysis (MSA) -- Step 5: Determine process capability -- Z scores and sigma shift -- Measure phase-gate review -- Manager's Checklist For Chapter 5 -- Analyze Phase: -- Analyze phase activities -- Analyze phase tools -- Ascertain and prioritize vital few causes of variation -- Transform the gaps into improvement projects -- Review the project with the champion -- Conduct an analyze phase-gate review -- Manager's Checklist For Chapter 6 -- Improve Phase: -- Improve phase activities -- Improve phase tools -- Correlation -- Regression analysis -- Design of experiments -- Planning the experiment (DOE) -- Conducting the experiment -- Running the experiment -- Analyzing the experiment results -- Review the project with the champion -- Conduct an improve phase-gate review -- Manager's Checklist For Chapter 7 -- Control Phase: -- Control phase steps and tools -- Control plan -- Statistical process control -- Control charts -- Contingency plans for out-of-control conditions -- Minimizing the potential for problems-mistake proofing -- Plan for transfer to process owners -- Communication plans -- Review the project with the champion -- Conduct a control phase-gate review -- Control phase deliverables -- Summary -- Manager's Checklist For Chapter 8 -- How To Sustain Six Sigma: -- Basic infrastructure requirements -- Communication plan -- Company culture -- Company cycles -- Reinforcement and control -- Manager's Checklist For Chapter 9 -- Six Sigma Proof Positive: -- Real final reports -- Case studies -- Training agendas -- Design for six sigma -- End-and the beginning -- Manager's Checklist For Chapter 10 -- Index.
Previous edition: 2002.
Includes index.
1 2
Keywords: Six sigma (Quality control standard); Quality control -- Statistical methods; Production management -- Statistical methods; Production management -- Statistical methods; Quality control -- Statistical methods; Six sigma (Quality control standard)